Are post-human technologies dehumanizing? Human enhancement and artificial intelligence in contemporary societies. Issue 5 (20th October 2022) - Al-Amoudi, Ismael
ABSTRACT: Post-human technologies, such as human enhancements and artificial intelligence, blur or displace the boundaries of our common humanity. While these technologies enhance many valuable human powers, there is limited philosophical discussion as to whether and how they can also be dehumanizing? To answer this question, I start from a philosophical discussion of the concept of 'dehumanization' and argue that it conflates three social mechanisms through which (i) human flourishing is impeded; (ii) subalterns are degraded; and (iii) automated processes replace typically human activities. Furthermore, I argue in realist fashion that we should consider both the natural powers harnessed by post-human technologies and the social contexts through which the latter are designed, produced, marketed and consumed. I then illustrate my thinking with three recent inquiries that I conducted on post-human technologies' dehumanizing potential. All three inquiries happen in the contemporary neo-liberal context, but each one foregrounds a distinct mechanism of dehumanization.